DEVELOPING SNAKE AND LADDER GAME TO TEACH STUDENTS SPEAKING SKILL FOR JUNIOR HIGH SCHOOL - Arfa'un Nadhiroh; Ahmad Saifudin; Tyas Alhim Mubarok (IKIP Siliwangi, 2024)
This research aims to develop a snake and ladder game as a learning media to teach English speaking skill. The snake and ladder game could be used as a solution to attract students' interest in learning English speaking skills. This study is an R&D research that used the ADDIE model. Qualitative data was obtained from the unstructured interview during the preliminary study meanwhile quantitative data was obtained from the questionnaire to validate the product by instrument expert, media expert, lesson expert, and student’s satisfaction. The instrument expert achieved 92,5%, the media expert achieved 91% and the lesson expert achieved 90%. All of those percentages are in the category “Very Valid”. The student’s satisfaction reached 86,2% which includes in the category “Very Satisfied”. In conclusion, the snake and ladder game could be used as learning media to teach speaking skill for junior high school to achieve learning objectives effectively.